Analisis Kebijakan Internalisasi Nilai-Nilai Pendidikan Ibadah di Sekolah - Ali Imran; M Iswantir (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2021)
As an effectiveness in the implementation of the internalizng policy of school education, the principal took two policies against teacers and students, namely first : an oral policy. Oral policy is a routine policy to increase discipline of teachers and students to pursue school programs, the nature of which is mostly situatoonal with the interest and needs of schools to internalize the virtues of religious eduction. Second, written policy. The most deaf policies are issued by the head of the school as a stakeholder to run written school programs for internising school education values. Such written policies exist as the teacher ordinance, student ordinance, teacher code of ethcs, the division of duty , teacher’s pick list, other written policies and policies that support the completion of the school’s education value internalization. As for the value of religious education that's internalized, like harsh, praying, stingy & prayer, read the Al-Qur’an and stare. In the process of implementing the policy of internalizing the value of the education of worship are conducted in a way ; 1) The formulation of the policy of internalizig the value of religious education. 2) Implementing og the internalizing policies of the values of religious education. 3) Evaluate the policy of the internalizing values of religious education.